Pemenuhan Regulasi Pelabelan Produk Industri Rumah Tangga Pangan (IRTP) di Bogor - Wiwit Arif Wijaya; Winiati Pudji Rahayu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
This research was aimed to evaluate the degree of ful llment of food product labels requirements by Small Medium Enterprises (SMEs) in Bogor compared with existing regulations (Indonesian Act Number 18 of 2012). Samples were chosen from three major SMEs products in Bogor, which were our products; grains and tubers products and softdrink and powdered beverages. Four groups of elements were tested: (1) technical labeling, (2) content format, (3) minimum information displayed, and (4) prohibited information. The results showed the level of fulfillment for those three types of products were: (1) technical labeling: 44, 45, and 73%, (2) format content: 75, 80, and 60%, (3) minimum information: 69, 64, and 66%; and 4) the level of fulfillment of not give prohibited information: 99, 100, 96%, respectively. The average level of fulfillment for those three types of products were 72, 72, and 74%, respectively. This low level of fulfillment showed that further development of SMEs is needed, especially about food labelling criteria according to the existing regulations.